2017
DOI: 10.3390/ijerph14020129
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Consumption and the Risk of Thyroid Cancer: A Systematic Review and Meta-Analysis

Abstract: An inverse association has been reported between coffee consumption and the risk of several cancers. However, the association between coffee and thyroid cancer is controversial. Thus, this study aimed to evaluate the association between coffee consumption and the risk of thyroid cancer through a systematic review and meta-analysis. Published studies were examined from PubMed, Embase, Cochrane Central, and the reference lists of the retrieved articles. The summary odds ratio (OR) for the association between cof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
(49 reference statements)
2
10
0
Order By: Relevance
“…A total of 24 studies about thyroid cancer and coffee were found, out of which a total of 10 studies were included after the exclusion of duplications (n=8) and 'not suitable' (n=14) articles. As documented in Table 3, no association between coffee consumption and thyroid cancer could be extracted from the population-based cohort studies (54)(55)(56) and meta-analyses of cohort and case-control studies (57,58). While a few case-control studies reported contradictory results.…”
Section: Q3: Is There a Relation Between Coffee Consumption And Thyromentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 24 studies about thyroid cancer and coffee were found, out of which a total of 10 studies were included after the exclusion of duplications (n=8) and 'not suitable' (n=14) articles. As documented in Table 3, no association between coffee consumption and thyroid cancer could be extracted from the population-based cohort studies (54)(55)(56) and meta-analyses of cohort and case-control studies (57,58). While a few case-control studies reported contradictory results.…”
Section: Q3: Is There a Relation Between Coffee Consumption And Thyromentioning
confidence: 99%
“…Only two studies have explored the effect of caffeinated or decaffeinated coffee consumption on thyroid cancer (TC) separately. The first one was a case-control study from German and detected that drinking decaffeinated coffee was associated with an increased risk of TC, whereas drinking caffeinated coffee had a preventive effect on thyroid cancer (57,61). The second one was a prospective cohort study from the USA with 167,720 non-white and white participants with 15.3 years follow-up period.…”
Section: Q3: Is There a Relation Between Coffee Consumption And Thyromentioning
confidence: 99%
“…Only few risk factors have been well-established for TC, such as history of having a benign thyroid tumor, exposure to ionizing radiation in childhood, and body fatness [4,5]. Dietary factors, such as nutrients and components (e.g., energy, polyunsaturated fatty acids, alcohol, and flavonoids) [68] and foods (e.g., fish, fruits and vegetables, coffee and tea) [912], have been suggested to play a role in TC etiology, although until now epidemiological evidence is still very limited and inconclusive [4].…”
Section: Introductionmentioning
confidence: 99%
“…[1]. In a rat model, co-promoting effects of high doses of caffeine in thyroid carcinogenesis have been described [16], while the role of caffeine in human thyroid carcinogenesis remains controversial [17].…”
Section: Results Implications and Interpretationmentioning
confidence: 99%